Between Order and Justice: Investments in Africa and Corporate International Responsibility in Swedish Media in the 1960s. (29th January 2019) - GLOVER, NIKOLAS
Abstract : This article analyzes how the public relations of multinational companies was affected by the double impact of decolonization and spread of television during the 1960s. It contributes to recent theoretical conceptualizations of corporate social responsibility by adding the dimension of home country stakeholders and the border-crossing character of corporate responsibility. The analysis deals with the changing media representations in Sweden of Swedish-owned firms in Liberia and South Africa before, during, and after what has been called the "postcolonial moment" (1960–1963). In its wake, Swedish industrialists faced a new policy problem: firms in overseas markets were no longer expected to do only what was legal in the host country but also what was considered right in their home country. The analysis follows the debates concerning this issue of corporate international responsibility throughout the 1960s, and how national business organizations and executives in firms such as the Liberian-American-Swedish Mining Company publicly sought to defend the role of Swedish foreign direct investment in Africa. The business community developed various public relations strategies to engage with its critics, professionalized their media relations, and organized international study tours for unions and politicians.